2021
DOI: 10.1186/s12876-021-02011-0
|View full text |Cite
|
Sign up to set email alerts
|

Independent associations of thyroid-related hormones with hepatic steatosis and insulin resistance in euthyroid overweight/obese Chinese adults

Abstract: Purpose The aim of the study is to explore the independent association of free triiodothyronine (FT3), free thyroxine (FT4) and thyroid stimulating hormone (TSH) with hepatic steatosis and insulin resistance. Methods A cross-sectional study of 88 overweight/obese adults who underwent anthropometric measurements [BMI, waist circumference (WC) and waist-to-height ratio (WHtR)], hepatic steatosis assessment (FibroScan) and thyroid-related hormones tes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
3
5
0
Order By: Relevance
“…But unlike the consistent ndings regarding thyroid dysfunction and NAFLD, discrepancies were shown in studies based on euthyroid subjects. For FT3, we found that high-normal FT3 was associated with increased risk of MAFLD, which is in line with a series of studies [12,[38][39][40][41]. As shown by Gu et al, high-normal FT3 was independently associated with a higher incidence of NAFLD in middle-aged and older euthyroid subjects [38].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…But unlike the consistent ndings regarding thyroid dysfunction and NAFLD, discrepancies were shown in studies based on euthyroid subjects. For FT3, we found that high-normal FT3 was associated with increased risk of MAFLD, which is in line with a series of studies [12,[38][39][40][41]. As shown by Gu et al, high-normal FT3 was independently associated with a higher incidence of NAFLD in middle-aged and older euthyroid subjects [38].…”
Section: Discussionsupporting
confidence: 90%
“…A large cross-sectional study in euthyroid subjects demonstrated a positive association between FT3 and the risk of NAFLD [40]. Also, in euthyroid overweight/obese adults, increased FT3 was indicated to be independently associated with higher risk of hepatic steatosis [39]. Contradictory results were indicated in a few studies.…”
Section: Discussionmentioning
confidence: 99%
“…53 Another study in euthyroid overweight/obese individuals indicated that increased FT3 was independently associated with higher risks of insulin resistance. 54 FT3 and FT4 positively and negatively correlated with HOMA-IR and atherogenic lipid profiles, respectively, in a euthyroid population with obesity. 55 In euthyroid subjects, serum FT4 was negatively associated with and TSH was positively associated with insulin resistance.…”
mentioning
confidence: 86%
“… 33 In the study by Ma et al, the mean (±SD) of age was 30.0±7.2 years old. 35 Thirdly, the disease characteristics of the study population were different among studies. In the studies by Tao et al, 37 Xu et al, 36 Ma et al 35 and van den Berg et al 32 euthyroid participants were selected.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Thirdly, the disease characteristics of the study population were different among studies. In the studies by Tao et al, 37 Xu et al, 36 Ma et al 35 and van den Berg et al 32 euthyroid participants were selected. In the study by Ding et al 34 patients with hepatitis B virus were enrolled.…”
Section: Discussionmentioning
confidence: 99%